Pengaruh Penggunaan Bambu Sebagai Pengganti Agregat Split terhadap Kuat Tekan Beton Ringan - Pujianto, As’at; Tajuddin, M. (Jurnal Semesta Teknika, 2012)
The use of bamboo as an aggregate replacement is one of the efforts to reduce the density and static load of structural elements, sincethe structural strength of bamboo is high. This study focus on the issue of the using bamboo as aggregate concrete with flowing method on a review of specific gravity and compressive strength of the concrete. This study uses bamboo as a percentage of the aggregate at 0% (normal), 20%, 40%, 60%, 80% and 100% of the conventional split and using additional silicafume aggregates. Specimens used in this study is the concrete cylinder (diameter 15 cm and height 30 cm). The identification and testing of tap density after 14 days of treatment.Results show that using more bamboo aggregate will result lower slump value, higher water absorption, decreasing in both specific gravity and compressive strength.